2024
DOI: 10.3389/fendo.2024.1327325
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes of the choroid and their correlations with visual acuity in diabetic retinopathy

Ruixia Jing,
Xiubin Sun,
Jimin Cheng
et al.

Abstract: ObjectiveTo investigate changes in the choroidal vasculature and their correlations with visual acuity in diabetic retinopathy (DR).MethodsThe cohort was composed of 225 eyes from 225 subjects, including 60 eyes from 60 subjects with healthy control, 55 eyes from 55 subjects without DR, 46 eyes from 46 subjects with nonproliferative diabetic retinopathy (NPDR), 21 eyes from 21 subjects with proliferative diabetic retinopathy (PDR), and 43 eyes from 43 subjects with clinically significant macular edema (CSME). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Jing et al [70] have described a noteworthy correlation between declining BCVA and CVI in individuals with DR. A reduction in CVI was the factor most strongly associated with visual impairment, according to multivariate regression analysis. This study revealed a correlation between the CVI and BCVA.…”
Section: Literature Review and Discussionmentioning
confidence: 98%
“…Jing et al [70] have described a noteworthy correlation between declining BCVA and CVI in individuals with DR. A reduction in CVI was the factor most strongly associated with visual impairment, according to multivariate regression analysis. This study revealed a correlation between the CVI and BCVA.…”
Section: Literature Review and Discussionmentioning
confidence: 98%